A replication plan for "Does social media reduce corruption?" (Information Economics and Policy, 2017) - Randall J. Hannum (Economics: The Open-Access, Open-Assessment E-Journal, 2018)
The importance of replicating economic research to improve the validity of findings has been the topic of an ongoing discussion, but there is not a consensus about what that means in practice. This article discusses a rationale for replicating a study and offers a plan of how one might go about approaching a replication of an actual study.
Keywords: B40; D73; 330; replications; corruption